DNA-Binding Proteins Essential for Protein-Primed Bacteriophage Φ29 DNA Replication - Salas, Margarita; Holguera, Isabel; Redrejo-Rodríguez, Modesto; de Vega, Miguel (Frontiers in Molecular Biosciences, 2016)
Bacillus subtilis phage Φ29 has a linear, double-stranded DNA 19 kb long with an inverted terminal repeat of 6 nucleotides and a protein covalently linked to the 5’ ends of the DNA. This protein, called terminal protein (TP), is the primer for the initiation of replication, a reaction catalyzed by the viral DNA polymerase at the two DNA ends. The DNA polymerase further elongates the nascent DNA chain in a processive manner, coupling strand displacement with elongation. The viral protein p5 is a single-stranded DNA binding protein (SSB) that binds to the single strands generated by strand displacement during the elongation process. Viral protein p6 is a double-stranded DNA binding protein (DBP) that preferentially binds to the origins of replication at the Φ29 DNA ends and is required for the initiation of replication. Both SSB and DBP are essential for Φ29 DNA amplification. This review focuses on the role of these phage DNA-binding proteins in Φ29 DNA replication both in vitro and in vivo, as well as on the implication of several B. subtilis DNA-binding proteins in different processes of the viral cycle. We will revise the enzymatic activities of the Φ29 DNA polymerase: TP-deoxynucleotidylation, processive DNA polymerization coupled to strand displacement, 3’-5’ exonucleolysis and pyrophosphorolysis. The resolution of the Φ29 DNA polymerase structure has shed light on the translocation mechanism and the determinants responsible for processivity and strand displacement. These two properties have made Φ29 DNA polymerase one of the main enzymes used in the current DNA amplification technologies. The determination of the structure of Φ29 TP revealed the existence of three domains: the priming domain, where the primer residue Ser232, as well as Phe230, involved in the determination of the initiating nucleotide, are located, the intermediate domain, involved in DNA polymerase binding, and the N-terminal domain, responsible for DNA binding and localization of the TP at the bacterial nucleoid, where viral DNA replication takes place. The biochemical properties of the Φ29 DBP and SSB and their function in the initiation and elongation of Φ29 DNA replication, respectively, will be described.